Is Vesicostomy Still a Contemporary Method of Managing Posterior Urethral Valves? - Aybike Hofmann; Maximilian Haider; Alexander Cox; Franziska Vauth; Wolfgang H. Rösch (MDPI AG, 2022)
In boys with posterior urethral valves (PUVs) the main treatment aim is to preserve long-term bladder and renal function. To determine the effectiveness of secondary vesicostomy in boys with PUVs, the medical records of 21 patients with PUV (2010-2019), divided into two groups (group I: valve ablation; group II: secondary vesicostomy), were reviewed regarding the course of serum creatinine, renal ultrasound, voiding cystourethrogram, urodynamics, postoperative complications, need of further surgery, and long-term solution. The median age of all patients at first follow-up was 11 (9-13) months and at last follow-up 64.5 (39.5-102.5) months. Despite a significant difference of the SWDR score (shape, wall, reflux, and diverticula) (p = 0.014), both groups showed no significant differences preoperatively. Postoperatively, serum creatinine (p = 0.024), grade of vesicoureteral reflux (p = 0.003), side of upper tract dilatation (p = 0.006), side of megaureter (p = 0.004), and SWDR score (p = 0.002) were significantly decreased in group II. Postoperative urodynamic measurements showed comparable results in both groups. Stoma complications were found in three (20%) patients (group II). Eight (53.3%) patients already received a closure of the vesicostomy. Seven out of eight (87.5%) patients were able to micturate spontaneously. Vesicostomy remains a reliable treatment option for boys with PUV to improve bladder function and avoid further damage to the urinary tract.